OPTIMALISASI PRODUKSI PANGAN LOKAL SAGU SEBAGAI PRODUK OLAHAN EKONOMIS DI KABUPATEN MERAUKE - Dawapa, Merry (Musamus University, 2019)
This study aims to determine the utilization of sago starch production on sago processed products at 5 times the potential of sago in merauke district. Data were analyzed descriptively, the population in this study were 5 districts with high productivity of sago farming in Merauke district, namely land sloping districts, curates, eligobel, ulilin and muting. Site selection by purposive sampling or deliberately. The results of the study showed that the five districts were not optimal for developing processed sago products due to lack of knowledge, expertise and limitations of technology adoption. Keywords: Local Farmers, Productivity, Optimization, Sago